METHODS OF USING INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING READING - Dowletmyradova Mahri (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
English is one of the most important languages, which have played role in the process of globalization and knowledge explosion. It is the most common means of communication throughout the globe. This is why it is termed as Link language, Global language as well as Lingua Franca. In Turkmen context, it is treated as EFL (English as a Foreign Language). Use of English language has become vital for better learning and earning. Therefore, it is necessary to teach English and develop English language skills among the students from school level. The government, NGOs and educational institutions are working at various levels and taking measures to ensure better ELT (English Language Teaching) and developing English language skills among the students. To teach English and develop English language skills various approaches and methods are in use in our country. However, most of them are traditional, less interesting, ineffective as well as less motivating. So, it is necessary to use modern approaches and tools of ICT (Information and Communication Technology) to develop better understanding and acquisition of basic skills i.e. LSRW (Listening, Speaking, Reading and Writing) of English language among the students at all levels. ICT has many things to offer to both teachers and students for the enhancement of their vocabulary and improvement of English language skills. Nowadays, ICT tools and approaches are being used widely due to their convenience, omnipresence, effectiveness and being economic. Some of these approaches, facilities and tools are CAI (Computer Assisted Learning), CALA (Computer Assisted Language Assessment), CALI ( Computer Assisted Language Instruction), CALL (Computer Assisted Language Learning), MALL (Mobile Assisted Language Learning), TELL (Technology Enhanced Language Learning). There are Blogs, Wiki, e-mail facility, Digital libraries, multimedia, mobile learning, free and open source software and social media, MOOCs (Massive Open Online Courses), Virtual classrooms, documentaries, Digital storytelling, Mobile Applications, i-Pads, Digital Notebooks, Tablets, Smart Phones, Recorded audio- video materials, Online spoken tutorials, Digital pronunciation dictionaries and others. Modern studies and researches show positive results of integration of ICT in the field of ELT and development of English language skills, especially in teaching reading These facilities have covered the way of individualized learning and provided freedom of learning anytime, anywhere according to needs and convenience of the learners.